2011
DOI: 10.1108/03074351111161600
|View full text |Cite
|
Sign up to set email alerts
|

Managerial views about dividend policy in Pakistan

Abstract: PurposeVery little is known about the influences on dividend decisions in Pakistan, despite the importance of the market in the region and the nation's non‐standard tax system. This study therefore aims to provide detailed evidence regarding this issue by examining the views of those charged with the decisions in practice.Design/methodology/approachThe study reports the findings from interviews with 23 Pakistani company officials about influences on their firms' dividend policies. A semi‐structured interview d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 31 publications
8
20
0
Order By: Relevance
“…In the same manner, interviewee C10, from the construction and real estate sector, opined that "the variable targeted when setting the amount of dividends to pay is the dividend per share dependent on the level of current earnings". This evidence of decline in the importance of target payout ratio in determining dividend payout is consistent with the recent findings reported by Brav et al (2005) for US firms, Chazi et al (2011) for UAE firms and Khan et al (2011) for Pakistani firms. However, some interviewees from financial firms did not appear to share these perceptions and believed that the target payout ratio was the starting point for their firm's dividend decisions.…”
Section: Dividend Conservatismsupporting
confidence: 91%
See 3 more Smart Citations
“…In the same manner, interviewee C10, from the construction and real estate sector, opined that "the variable targeted when setting the amount of dividends to pay is the dividend per share dependent on the level of current earnings". This evidence of decline in the importance of target payout ratio in determining dividend payout is consistent with the recent findings reported by Brav et al (2005) for US firms, Chazi et al (2011) for UAE firms and Khan et al (2011) for Pakistani firms. However, some interviewees from financial firms did not appear to share these perceptions and believed that the target payout ratio was the starting point for their firm's dividend decisions.…”
Section: Dividend Conservatismsupporting
confidence: 91%
“…By implication, this perception is consistent with the notion that firms pay dividends from earnings and reinforces the conclusion of Benartzi et al (1997) who documented a strong concurrent link between current earnings and dividend changes in their empirical analysis of changes in dividends in the US. The evidence that current earnings is the most important factor in crafting a firm's dividend policy is consistent with evidence of Lintner (1956), Baker and Smith (2006) and Khan et al (2011) where current earnings was found to be the most important determinant of payout levels. The views of the respondents also supports (although less strongly) the explicit implications of the Lintner's (1956) theoretical model of dividend policy which states that the current dividend levels are based on both the current earnings and the pattern of past dividends.…”
Section: Factors That Drive Dividend Decisionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the year 2008, a cap was also implemented in order to secure the investors against the higher variations in the share prices. The rising trend was later observed at the end of 2009 (Khan, Burton, & Power, 2011). The KSE has seen volatility over the past decades mainly due to economic and political instability ).…”
Section: Background Of the Karachi Stock Exchange (Kse)mentioning
confidence: 95%